Gambaran Independent dan Interdependent Self-Construal pada Mahasiswa Indonesia - Marissa Chitra Sulastra; Vida Handayani (Humanitas (Jurnal Psikologi), 2021)
This study aims to get self-construal description among Indonesian student. Indonesia has collectivitic culture which group conformity is important in society. When collectivistic culture internalized into way of seeing self, it will form interdependent self-construal. This study used a sample of 521 Indonesian students with a non-probability sampling technique who registered as student, Indonesian citizens, live in Indonesia and willing to fill out questionnaire. The instrument used in this study was translated from Singelis's Self-Construal questionnaire (1994). The result of data analysis using Wilcoxon test showed that Indonesian students have equal independent and interdependent self-construal (Z = -0,712, sig = 0,477). It can be concluded that Indonesian students see themselves as a separate part and an integrated part with others. This study can be used as a base for further research and give information that Indonesian students internalize collectivistic and individualistic culture as a way of seeing themselves. Keywords: Self-Construal, Cross-Cultural Psychology, Indonesia, Sundanese Culture